2020
DOI: 10.3390/jcm9103308
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Endothelial Cell Metabolism by Inhibition of Pyruvate Dehydrogenase Kinase and Glutaminase-1

Abstract: Targeting endothelial cell (EC) metabolism should impair angiogenesis, regardless of how many angiogenic signals are present. The dependency of proliferating ECs on glucose and glutamine for energy and biomass production opens new opportunities for anti-angiogenic therapy in cancer. The aim of the present study was to investigate the role of pyruvate dehydrogenase kinase (PDK) inhibition with dichloroacetate (DCA), alone or in combination with the glutaminase-1 (GLS-1) inhibitor, Bis-2-(5-phenylacetamido-1,3,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In addition, lower concentrations of DCA (6.25 and 12.5 mM) did not affect the HUVECs tube formation. These findings are consistent with a report by Schoonjans and coworkers, who demonstrated that 5 mM and 10 mM DCA did not affect HUVECs' tube formation in vitro [29]. In agreement with our data, DCA caused a reduction in the tumor microvessel density in treated rats, in which HIF1α suppression was also reported within the tumor cells [30].…”
Section: Discussionsupporting
confidence: 94%
“…In addition, lower concentrations of DCA (6.25 and 12.5 mM) did not affect the HUVECs tube formation. These findings are consistent with a report by Schoonjans and coworkers, who demonstrated that 5 mM and 10 mM DCA did not affect HUVECs' tube formation in vitro [29]. In agreement with our data, DCA caused a reduction in the tumor microvessel density in treated rats, in which HIF1α suppression was also reported within the tumor cells [30].…”
Section: Discussionsupporting
confidence: 94%
“…At present, there is no definite evidence to prove the role of glutamine metabolism in TECs. It has been studied that the combination of pyruvate dehydrogenase kinase inhibition with dichloroacetate and glutaminase‐1 (GLS‐1) inhibitor, bis‐2 ‐ (5‐phenylacetamide‐1,3,4‐thiadiazol‐2‐yl) ethyl sulfide (BPTES) is conducive to the normalization of tumour blood vessels 84 …”
Section: Differences Between Tumour Endothelial Cells and Normal Endo...mentioning
confidence: 99%
“…Glutamine metabolism (glutaminolysis), which involves the deamination of glutamine to glutamate by the enzyme glutaminase (GLS1), serves as a critical process in replenishing the carbon intermediates for maintaining the mitochondrial TCA cycle [ 26 ]. A stiff matrix, which mimics stiffness in hypertensive pulmonary arterioles, activates GLS1 and glycolysis, decreases oxidative phosphorylation, and restores cell proliferation in human pulmonary arterial endothelial cells than a soft matrix (mimicking stiffness in non-diseased pulmonary arterioles in rodents), whereas inhibition of GLS1 reduces glutaminolysis and attenuates cell proliferation [ 27 29 ]. Combined inhibition of GLS1 and PDH reduces endothelial proliferation, migration, and tube formation; these effects are coupled with normalized mitochondrial oxidation [ 27 ].…”
Section: Glycolysismentioning
confidence: 99%